Contagion - Bowman, Erin (HarperTeen, an imprint of HarperCollinsPublishers, 2018)
Responding to a distress call on the distant planet of Achlys, Thea Sadik and her search-and-rescue crew are confronted by a zombie-like outbreak that forces them to uncover a monstrous enemy.